DWUGŁOS W SPRAWIE POJĘCIA ŚWIADCZENIA W POLSKIM PRAWIE CYWILNYM – WYMOGI ŚWIADCZENIA - Antas, Marek; Łukasiewicz, Jakub M. (Zeszyty Prawnicze, 2016)
This paper has been constructed on the basis of a dialogue between J.M. Łukasiewicz and M. Antas. In its first part the authors explain the notion of behaviour that satisfies a creditor’s interest which deserves legal protection and its relation to the notion of behaviour consistent with the content of an obligation, on the example of provisions concerning the valorisation of a service. They point out the inconsistency of the notions of due service and undue service under Article 410 of the Polish Civil Code. They also argue that every service leads to a benefit. Their discussion is concluded by an open question: to which category should the execution of a service be attributed – factual actions or legal actions?